Dental markers of poverty: Biocultural deliberations on oral health of the poor in mid‐nineteenth‐century Ireland. Issue 4 (3rd October 2018) - Geber, Jonny; Murphy, Eileen
Abstract: Objectives: Despite subsisting on a low‐cariogenic diet comprising virtually nothing more than potatoes and dairy products, poor oral health affected the quality of life for the poor of nineteenth‐century Ireland. This study investigates potential biocultural reasons that may explain why this was the case. Material and Methods: A total of 6, 860 teeth and 9, 889 alveoli from 363 permanent dentitions from the skeletal remains of impoverished adult Irish males and females who died between 1847 and 1851 in the Kilkenny Union Workhouse were examined for evidence of dental caries, periodontal disease and ante‐mortem tooth loss. Caries rates were quantified and assessed by crude prevalence, frequencies, corrected caries rates and a t‐health index, and evaluated by sex and age groups. Results: A higher rate of caries was present among 18–25‐year‐old males than females, while the opposite relationship was evident for older age groups. The prevalence rates of periodontal disease and ante‐mortem tooth loss increased with age. When assessed by corrected caries rates, tooth decay is observed at a lower rate compared to contemporaneous lower to upper‐class population samples from London. Discussion: Despite being low cariogenic foods, the potato starch and milk lactose of a nineteenth‐century Irish laborer's diet would have lowered oral pH‐values thereby increasing the risk of bacterial fermentation in dental plaque resulting in caries. Nutritional features alone cannot explain the high rates of dental caries observed in the Kilkenny workhouse population sample, however, and lifestyle factors, particularly habitual clay‐pipe smoking, is considered a significant cause of poor oral health.